2019
DOI: 10.3390/molecules24173101
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Antimicrobial Potential of Extracts Obtained from Thymus marschallianus Willd

Abstract: Thymus marschallianus Willd. is a Lamiaceae species spread in a large variety of habitats worldwide. The aim of the present research was to analyse two different samples belonging to this species, one obtained from the spontaneous flora and one from culture. The total polyphenols, flavonoids, and phenolic acid contents were spectrophotometrically determined. Qualitative and quantitative analysis of polyphenols was performed by an HPLC-DAD-ESI (+)-MS method. For the antibacterial assay, the well-diffusion and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 40 publications
6
28
0
2
Order By: Relevance
“…979, from which sample TMC was obtained). The taxonomic identification of the species was performed by Nina Ciocârlan, PhD, from the Botanical Garden of the Moldavian Science Academy, where voucher specimens are deposited in the Herbarium ( Niculae et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…979, from which sample TMC was obtained). The taxonomic identification of the species was performed by Nina Ciocârlan, PhD, from the Botanical Garden of the Moldavian Science Academy, where voucher specimens are deposited in the Herbarium ( Niculae et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thymus (thyme) is one of the most important genus belonging to the Lamiaceae family (Niculae et al, 2019). This family is known worldwide for its traditional uses, in the treatment of different pathologies, being also used since ancient times for their importance as aromatic plants (Nabavi et al, 2015), that are assigned to their composition in essential oils (Tohidi et al, 2019) and phenolic compounds (Raudone et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most important flowering plant families, the Lamiaceae family is one of the largest, comprising numerous species that are known for their biological activities or for their use in different branches related to economy [ 1 , 2 , 3 ]. Species belonging to the genera Salvia [ 4 ], Melissa [ 5 ] or Thymus [ 6 ] are the most well known, being widely used in different forms for the treatment of numerous pathologies, but also for their nutritional or economical values [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC analysis revealed that this extract is composed of six main components. Most of them have the anti-oxidation, anti-inflammatory, antibacterial, and antitumor effects (23)(24)(25)(26)(27)(28)(29). Interestingly, three of them (methyl Rosmarinate, Luteolin and Diosmetin) are capable of suppressing cell proliferation.…”
Section: Discussionmentioning
confidence: 99%